Unmasking the Outcomes of Social Cash Transfer and Non-Contributory Pensions for Elderly Persons: A Systematic Literature Review (African Multidisciplinary Journal of Research, 2025)
The study aimed at investigating on the social protection programmes for the elderly by assessing peer-reviewed articles that covered cash transfers for the elderly in the period.  PICOT and PRISMA frameworks were adopted to guide the literature of the articles that were published on cash transfers in the period 2019 to 2024. The findings were that; the studies had no commonalities on research objectives, research designs, research hypothesis, inferential statistical measurements even for similar outcomes. The scope of the studies in Sub-Saharan Africa should be expanded to include other countries. In Southern African countries like Zambia and Malawi, most studies were non-empirical and thus dropped. The utilisation of grey literature to enrich the review would fundamentally improve the discussions and the outcomes. Future studies should attempt to apply other participatory techniques such as ethnography and storytelling to capture the sociological components. It should also be keen to properly target samples of social protection beneficiaries and improving on generalisability.